Anatomical Features of Scutellaria tonkinensis Doan in Vietnam - Xuyen, Do Thi; Hao, Ngo Thu; Ve, Doan Van; Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 4, 2022)
Scutellaria L. is a genus of flowering plant in the Lamiaceace. The genus includes about 350 species commonly known as skullcaps. Scutellaria is widespread in temperate regions and tropical mountains including Europe, North America and East Asia. 15 species belonging to Scutellaria genus were recorded in Vietnam. The perennial herb Scutellaria tonkinensis Doan is an endemic species of Vietnam and is recorded in Lao Cai and Vinh Phuc provinces. In this study, anatomical charateristics of this species using double-staining method have been investigated. The anatomical characteristics indicate that S. tonkinensis Doan adapt to a habitat with high moisture and intensive insolation.